Analysis of the software testing department of the company “Starky’s Club” - Chyzhykov, Yevhenii; Doucek, Petr, 1960-; Oškrdal, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
Managing the information technology is one of the main parts all of the IT companies today. It includes maintaining all of the activities in the company as efficient as possible, achieving the deadlines, meeting the customer expectations and prioritise the tasks. Testing is also a big part of each development process. In today’s world IT companies are separated into two different types of approaches – Waterfall and Agile. There are still a lot of space for both approaches in modern world, but, of course, they do have their strong and weak sides. This Diploma thesis describes basics of information technology management, differences between Waterfall and Agile, basics of testing and its importance. I tried to prove my own idea, why testing department should have the biggest influence on managing the information technology at least in small or medium companies. In the practical part, current situation of the testing department in company “Starky’s Club” was analyzed, there were found the best ways and approaches of improving it and explained the best way to implement testing processes in Agile development. The analysis in this Diploma thesis is unique, combines different resources and approaches and shows the way to implement those ideas in a real project.
Vedoucí práce: Petr Doucek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses